Sapta Darma Belief System: Concept Of Diversity And Strategies For Navigating Social Change - Siregar, Yusdinal Rizki; Naldo, Jufri; Ismahani, Siti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to explore the concept of diversity within the Sapta Darma belief system, and the strategies adopted by its adherents to navigate social change. This research employs a library research approach. According to Mestika Zed, library research involves a systematic process of collecting, reading, annotating, and analyzing data from various scholarly sources. It encompasses the examination of reference books, prior research findings, and academic literature to establish a theoretical foundation for the study. Literature review is also used as a data collection technique by analyzing books, notes, and reports relevant to the research problem. The findings indicate that the Sapta Darma belief system upholds a profound understanding of diversity, reflected in its principles of tolerance and inclusivity toward different societal groups. The Sapta Darma community employs adaptive and flexible strategies to respond to social, political, and cultural transformations while preserving the essence of its teachings. These adaptation strategies include modifications in worship practices, societal engagement, and the integration of technological advancements, particularly in the use of social media. This research provides new insights into how local belief systems sustain their existence and remain resilient amid continuous societal changes.